The Influence of E-Servicescape, E-Trust, and E-Service Quality on Customer Satisfaction on the E-Commerce: (Study of Shopee Users in Surabaya City) - Safira, Shahna Naila; Nirawati, Lia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Technological advances have led to the emergence of the internet network, transforming business transactions such as e-commerce; one example is Shopee. This research aims to evaluate the impact of e-servicescape, e-trust, and e-service quality on customer satisfaction among Shopee application users in the city of Surabaya. By sending surveys using Google Form, data was gathered electronically. Surabaya city inhabitants make up the study's population. The purposive sampling approach yielded a sample size of 135 respondents for this investigation. Multiple linear regression, the F test, the t test, coefficient of determination, validity and reliability analysis, and classical assumptions are all used in this study plan. Based on the research findings, customer satisfaction is significantly impacted by e-service quality, e-trust, and e-servicescape all at the same time. At a significance level below 0.05, e-trust, e-service quality, and e-servicescape all have a somewhat significant impact on customer satisfaction. This indicates that increased consumer satisfaction with the Shopee application is correlated with improved e-servicescape, e-trust, and e-service quality offered by Shopee.